Ictiólogos de la Argentina: Víctor Angelescu - Lopez, Hugo Luis (2012)
This series will include all those people who, by means of their contributions, great and small, played a part in the consolidation of ichthyology in Argentina. The general plan of this work consists of individual factsheets containing a list of works by each author, along with reference bibliography and, whenever possible, personal pictures and additional material. The datasheets will be published primarily in chronological order, although this is subject to change by the availability of materials for successive editions. This work represents another approach for the recovery and revalorization of those who set the foundations of Argentine ichthyology while in diverse historical circumstances. I expect this to be the beginning of a major work that achieves the description of such a significant part of the history of natural sciences in Argentina.